Product development in Islamic banks - Ahmed, Habib (Edinburgh guides to Islamic finance., 2011)
A systematic study of the process of developing Islamic financial products for banks. Islamic banking began in the 1970s with the aim of providing financial services compatible with Islamic law. Driven by market forces it has grown rapidly in Muslim countries and in international financial sectors. It is projected to grow at an annual rate of 15-20% and a key factor determining this future growth is the availability of new products that will satisfy the needs of various segments of society. While other texts discuss the basic principles and contracts used in Islamic banking and finance, few discuss how these can be used to develop financial products. This book fills that gap, starting with the basic principles that form the building blocks of contemporary Islamic financial products and then discussing the more intricate issues relating to product development processes. Key Features Discusses the different stages of the product development cycle in detail Includes case studies showing the structures of various products Critically evaluates the issues related to product development including the types of products used by Islamic banks and the approaches adopted in developing them The author is well-positioned to write this text, having been an economist at the Islamic Development Bank Group in Saudi Arabia (1999-2007)